Structural equation modeling of emotional exhaustion and life satisfaction in college students - Reyna Martínez, Mónica (2025)
Academic emotional exhaustion is a decisive factor of individual stress that can affect the psychological well-being and academic performance of university students. Life dissatisfaction has been identified as a variable influencing this phenomenon, which may act either as a risk or protective factor. The objective of this study was to evaluate a structural equation model explaining how the independent variables—life dissatisfaction and academic emotional exhaustion—affect levels of stress, anxiety, and depression among university students. It was a cross-sectional, correlational, and explanatory study with a sample of 207 Mexican university students (M = 21.08 years, SD = 5.18), of whom 50.7% were women and 49.3% men. The Satisfaction with Life Scale, the Academic Emotional Exhaustion Scale, and the DASS-21 Scale were employed. Descriptive, internal consistency, correlational, and normality analyses were conducted, followed by structural equation modeling. The results indicate that life dissatisfaction influences academic emotional exhaustion, explaining 9% of its variance. The analyzed factors explained 50% of the variance in stress, 62% in depression, and 69% in anxiety. The model showed adequate fit indices (χ² = 6.3, p = .09, CMIN/DF = 2.13, GFI = .988, RMSEA = .074). These findings highlight the need to implement psychological support programs in universities to mitigate the impact of emotional exhaustion on mental health and academic performance.